Islamic Capital Market Research: A Bibliometric Visualization based on Scopus ‎Database (2000-2022) - TAHIR, MUHAMMAD; FAROOQ, UMAR; IFTIKHAR, HAFIZ AHMAD (International Journal of Islamic Economics and Governance, 2022)
The Islamic capital market has emerged as a critical player in Islamic social ‎finance, providing a Shariah-compliant alternative to traditional capital markets for ‎Muslim customers. With a plethora of research in the field of Islamic finance, ‎there is a growing body of empirical views regarding new enhancements in the ‎Islamic capital market. Thus, it is imperative to understand the emergence of ‎research in this area to conduct further studies on various aspects. In this study, ‎data was extracted using the Scopus database, with "Islamic Capital Market" as the ‎reference in "Article title, Abstract, and keywords," specifying the duration from ‎‎2000 to 2022. Various software tools such as VOS viewer, R studio, Biblioshiny, ‎and Excel were employed to apply bibliometric methods for a comprehensive ‎analysis of past research on Islamic Capital Market through different visualization ‎methods.‎ The findings reveal a clear research gap in the existing literature on Islamic Capital ‎Market. While available research covers historical background and general ‎discussions, significant areas, such as technology’s use for innovation in the ‎Islamic capital market, are not widely discussed. It is also noted that until 2011, ‎there was no significant increase in research in this field. However, since then, ‎numerous empirical and theoretical studies have been conducted, and it is expected ‎that this growth will continue in the coming years. This study contributes to the ‎understanding of the current state of research in the Islamic capital market and ‎provides a basis for future research in this area. ‎